3-2(x+1)=2(1-x)

Simple and best practice solution for 3-2(x+1)=2(1-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-2(x+1)=2(1-x) equation:



3-2(x+1)=2(1-x)
We move all terms to the left:
3-2(x+1)-(2(1-x))=0
We add all the numbers together, and all the variables
-2(x+1)-(2(-1x+1))+3=0
We multiply parentheses
-2x-(2(-1x+1))-2+3=0
We calculate terms in parentheses: -(2(-1x+1)), so:
2(-1x+1)
We multiply parentheses
-2x+2
Back to the equation:
-(-2x+2)
We add all the numbers together, and all the variables
-2x-(-2x+2)+1=0
We get rid of parentheses
-2x+2x-2+1=0
We add all the numbers together, and all the variables
-1!=0
There is no solution for this equation

See similar equations:

| x+0.1x=64579.53 | | 1/4n-3=7 | | 6x+30=3x+4x | | 3(3w+1)/4=7 | | 34=-7(4d+3) | | 3(6y+7)+5y=13 | | 5x+17=-9x+56+27x | | 3/5x-9=45 | | 3+z=5 | | 2x+12=2/5x | | 8-5x=-52 | | X(8+x)=3.5(6+3.5) | | 5{x-6}=2{x+3} | | 8x/3-8=7 | | y=10(0)+10 | | 4x-11=40 | | 17+c=26-2c | | 2x-2x-4+2=2+-2+5x | | 79x+8x=5x | | x-11*4=40 | | 5+0.142857x=7 | | 3(4s+5)=171 | | 6x-24/5=-36 | | 2x+(-4)=-14 | | 5+(1/7)x=7 | | 7(u+2)=49 | | -2(3x+4)=-4(x-2)-2x | | 4(q-4)=40 | | 4x=1600 | | 4(e+2)=20 | | 270=127-y | | 8x=5- |

Equations solver categories